Composite negative electrode material and preparation method and application thereof

By using a composite structure of a nitrogen-doped hard carbon core and carbon nanotubes in CuCo2O4 material, combined with CuCo2O4/C composite material, the stability and rate performance problems caused by volume expansion of CuCo2O4 material are solved, and the circulation of lithium-ion batteries is significantly improved. and rate performance.

CN119208550APending Publication Date: 2024-12-27CHINA FAW CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411112901.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing CuCo2O4 material expands too much during charging and discharging, resulting in poor stability and rate performance, making it difficult to meet the practical application needs of lithium-ion batteries.

Method used

The composite structure of a nitrogen-doped hard carbon core and coated carbon nanotubes is combined with CuCo2O4 and carbon materials, and the matrix material is prepared by the pyrolytic polyurethane foam template method, and CuCo2O4/C composite material is grown on its surface to form a porous structure. Improve conductivity and capacity retention capabilities.

Benefits of technology

It achieves efficient lithium ion transmission and structural stability, improves the cycle performance, rate performance and safety performance of the battery, with a capacity retention rate greater than 94%, and a Coulomb efficiency greater than 90%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004992799200000221
    Figure BDA0004992799200000221
  • Figure BDA0004992799200000231
    Figure BDA0004992799200000231
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a composite negative electrode material as well as a preparation method and application thereof. The invention provides a composite negative electrode material. The composite negative electrode material comprises a base material and a composite structure located on the surface of the base material, the base material comprises a nitrogen-doped hard carbon inner core and a carbon nano tube coating the nitrogen-doped hard carbon inner core; the composite structure comprises CuCo2O4 and a carbon material. In the composite negative electrode material disclosed by the invention, the nitrogen-doped hard carbon core has relatively light weight, obvious skeleton structure and good flexibility; the carbon nanotubes on the surface of the nitrogen-doped hard carbon core form a cross-linked porous skeleton, so that efficient ion transmission and structural stability are achieved; the CuCo2O4 in the composite structure is matched with the carbon material, so that the composite structure has good conductivity, high capacity and good capacity retention capability and rate capability, can effectively promote the transfer of lithium ions, and can bear high stress caused by continuous intercalation / deintercalation of Li < + >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a composite negative electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are considered to be one of the major breakthroughs in the field of electrochemical energy storage in recent decades due to their advantages such as low cost, long cycle performance, small size, high energy density, large reversible capacity, and no memory effect. Their practical applications include electric and hybrid vehicles, portable electronic devices, and smart grids.

[0003] So far, graphite has been considered as a commercial material for lithium-ion battery anodes. However, traditional graphite anodes have problems such as low theoretical capacity and low efficiency, which makes it difficult to meet the growing demand for energy storage. Therefore, it is imperative to develop and manufacture new anode materials with excellent electrochemical properties. Seeking high-performance negative electrode materials to replace commercial graphite electrodes is of great significance in both scientific research and practical applications. Other potential anode materials, such as transition metals, silicon, sulfur, and their compounds or composites, as conversion-type negative electrode materials, have been widely explored and valued by the academic community due to their high theoretical capacity. Among them, transition metal oxides such as nickel cobalt oxide, magnesium cobalt oxide, and copper cobalt oxide have attracted much attention as promising negative electrode materials. They have the advantages of high theoretical capacity, good safety, and low cost, and are expected to replace industrial graphite. Among them, copper cobalt oxide has good environmental protection and low price compared with several other oxides, and is considered to be a promising negative electrode material for lithium-ion batteries. However, as the research on transition metal oxide negative electrode materials deepens, researchers have found that there are some inevitable defects. For example, transition metal oxide-based negative electrode materials have poor cycle performance and rate performance due to excessive volume expansion during charging and discharging, which seriously hinders their practical application.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] An object of the present invention is to provide a composite negative electrode material to solve the technical problem in the prior art that CuCo2O4 has poor stability and rate performance due to excessive volume expansion during charging and discharging.

[0006] Another object of the present invention is to provide a method for preparing the composite negative electrode material, which can obtain a composite negative electrode material with excellent electrochemical performance through the coordination of various steps.

[0007] Another object of the present invention is to provide a negative electrode sheet.

[0008] Another object of the present invention is to provide a battery.

[0009] Another object of the present invention is to provide an electrical device.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] A composite negative electrode material comprises a base material and a composite structure located on the surface of the base material; the base material comprises a nitrogen-doped hard carbon core and carbon nanotubes coating the nitrogen-doped hard carbon core; the composite structure comprises CuCo2O4 and a carbon material.

[0012] In some embodiments, the nitrogen-doped hard carbon core includes a spherical structure.

[0013] In some embodiments, the carbon nanotubes are in a cross-linked network structure.

[0014] In some embodiments, the capacity retention rate of a battery prepared from the composite negative electrode material after 100 cycles at 0.1 A / g is greater than 94%.

[0015] In some embodiments, the coulombic efficiency of a battery prepared from the composite negative electrode material after 100 cycles at 0.1 A / g is greater than 90%.

[0016] The method for preparing the composite negative electrode material as described above comprises the following steps:

[0017] The polyurethane foam is immersed in a carbon nanotube dispersion to obtain a polyurethane foam loaded with carbon nanotubes, and the polyurethane foam loaded with carbon nanotubes is subjected to a first heat treatment to obtain a matrix material; the matrix material is immersed in a mixed solution formed by a soluble copper source, a soluble cobalt source, an organic solvent and an organic ligand, and a composite negative electrode material is obtained after a second heat treatment.

[0018] In some embodiments, the method for preparing the carbon nanotube dispersion specifically includes: mixing the carbon nanotubes with a sulfuric acid solution and subjecting the mixture to condensation reflux treatment, then mixing the carbon nanotubes with concentrated nitric acid, cooling the mixture and washing the mixture, collecting the solids and mixing the solids with water to obtain a carbon nanotube dispersion.

[0019] In some embodiments, in the method for preparing the carbon nanotube dispersion, the usage ratio of carbon nanotubes, sulfuric acid and concentrated nitric acid is (200-400) mg: (100-200) mL: (35-60) mL.

[0020] In some embodiments, in the method for preparing the carbon nanotube dispersion, the mixing treatment time is 12 to 48 hours.

[0021] In some embodiments, in the method for preparing the carbon nanotube dispersion, the temperature of the condensation reflux treatment is 60 to 100° C., and the time of the condensation reflux treatment is 1 to 5 hours.

[0022] In some embodiments, the concentration of the carbon nanotube dispersion is 1 to 4 mol / L.

[0023] In some embodiments, the mass ratio of the polyurethane foam to the carbon nanotubes is 1:(1-4).

[0024] In some embodiments, the shape of the polyurethane foam comprises a cube, and the volume of the polyurethane foam is 1 to 1.5 cm 3 .

[0025] In some embodiments, the temperature of the first heat treatment is 450-550° C., and the time of the first heat treatment is 30-90 min.

[0026] In some embodiments, the first heat treatment is performed under protective gas conditions, and the heating rate of the first heat treatment is 5 to 10° C. / min.

[0027] In some embodiments, before the first heat treatment, the first drying treatment is further included; the temperature of the first drying treatment is 60 to 80° C., and the time of the first drying treatment is 12 to 24 hours.

[0028] In some embodiments, the soluble copper source includes at least one of Cu(NO3)2·3H2O and CuSO4.

[0029] In some embodiments, the soluble cobalt source includes at least one of Co(NO3)2·6H2O and CoSO4.

[0030] In some embodiments, the soluble cobalt source includes Co(NO3)2.6H2O.

[0031] In some embodiments, the organic ligand comprises 2-methylimidazole.

[0032] In some embodiments, the usage ratio of the soluble copper source, the soluble cobalt source, the organic ligand and the organic solvent is (0.2-0.8) mmol: (0.5-1.6) mmol: (15-20) mmol: (25-35) mL.

[0033] In some embodiments, the soaking time is 10 to 15 hours.

[0034] In some embodiments, the temperature of the second heat treatment is 300-400° C., and the time of the second heat treatment is 1-2 hours.

[0035] In some embodiments, the second heat treatment is performed under protective gas conditions, and the heating rate of the second heat treatment is 2 to 10° C. / min.

[0036] In some embodiments, before the second heat treatment, the second drying treatment is further included; the temperature of the second drying treatment is 60 to 80° C., and the time of the second drying treatment is 12 to 24 hours.

[0037] A negative electrode sheet comprises the composite negative electrode material, or the composite negative electrode material prepared by the method for preparing the composite negative electrode material.

[0038] A battery comprises the negative electrode sheet.

[0039] An electrical device comprises the battery.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] (1) In the composite negative electrode material of the present invention, the nitrogen-doped hard carbon core of the matrix material has a light weight, a distinct skeleton structure, good flexibility, and forms an effective three-dimensional conductive structure throughout the interior, which provides a good conductive substrate for constructing a three-dimensional electrode; the carbon nanotubes on the surface of the nitrogen-doped hard carbon core form cross-linked carbon nanotube bundles, and this cross-linking forms many pores, thereby forming a porous skeleton, which is conducive to the diffusion of electrolytes, has efficient ion transport and structural stability, and can not only effectively promote the transport of lithium ions, but also withstand Li + The high stress caused by continuous embedding / de-embedding. The CuCo2O4 and carbon materials in the composite structure have good conductivity, high capacity, good capacity retention and rate capability, which can effectively promote the transport of lithium ions and can withstand Li + High stress caused by continuous embedding / de-embedding.

[0042] (2) The preparation method of the composite negative electrode material of the present invention uses polyurethane foam as a template and a sacrificial template method to prepare a matrix material (nitrogen-doped hard carbon balls interconnected by carbon nanotubes), and then grows a MOF-derived CuCo2O4 / C composite material on the matrix material by an in-situ growth method. The MOF-derived CuCo2O4 / C composite material has good conductivity, high capacity, good capacity retention and rate capability on the surface of the matrix material, can effectively promote the transport of lithium ions, increase the number of ion diffusion paths, and can withstand Li + High stress caused by continuous embedding / de-embedding.

[0043] (3) The battery of the present invention has excellent rate performance, cycle performance and safety performance. DETAILED DESCRIPTION

[0044] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0045] According to one aspect of the present invention, the present invention relates to a composite negative electrode material, including a base material and a composite structure located on the surface of the base material; the base material includes a nitrogen-doped hard carbon core and carbon nanotubes coating the nitrogen-doped hard carbon core; the composite structure contains CuCo2O4 and carbon material.

[0046] In the composite negative electrode material of the present invention, the nitrogen-doped hard carbon core of the matrix material has a light weight, a distinct skeleton structure, good flexibility, and forms an effective three-dimensional conductive structure in the entire interior, which provides a good conductive substrate for constructing a three-dimensional electrode; the carbon nanotubes on the surface of the nitrogen-doped hard carbon core form mutually cross-linked carbon nanotube bundles, and the cross-linking forms a large number of pores, thereby forming a porous skeleton. The pore structure is conducive to the diffusion of electrolytes, has efficient ion transmission and structural stability, can not only effectively promote the transport of lithium ions, but also can withstand Li + The high stress caused by continuous embedding / de-embedding. The CuCo2O4 and carbon materials in the composite structure have good conductivity, high capacity, good capacity retention and rate capability, which can effectively promote the transport of lithium ions and can withstand Li + High stress caused by continuous embedding / de-embedding.

[0047] In some embodiments, the nitrogen-doped hard carbon core includes a spherical structure.

[0048] In some embodiments, the carbon nanotubes are in a cross-linked network structure.

[0049] In some embodiments, the capacity retention rate of a battery prepared from the composite negative electrode material after 100 cycles at 0.1 A / g is greater than 94%.

[0050] In some embodiments, the coulombic efficiency of a battery prepared from the composite negative electrode material after 100 cycles at 0.1 A / g is greater than 90%.

[0051] According to another aspect of the present invention, the present invention also relates to a method for preparing a composite negative electrode material, comprising the following steps:

[0052] The polyurethane foam is immersed in a carbon nanotube dispersion to obtain a polyurethane foam loaded with carbon nanotubes, and the polyurethane foam loaded with carbon nanotubes is subjected to a first heat treatment to obtain a matrix material; the matrix material is immersed in a mixed solution formed by a soluble copper source, a soluble cobalt source, an organic solvent and an organic ligand, and a composite negative electrode material is obtained after a second heat treatment.

[0053] The present invention prepares the matrix material by the method of pyrolyzing a sacrificial polyurethane foam template, which has the advantages of simple process, controllable shape, low cost, etc. Through the first heat treatment, hard carbon balls doped with N element are obtained. The source of nitrogen is mainly due to the generation of some nitrogen-containing groups in the process of pyrolyzing polyurethane foam, and at the same time, they are enriched in the oxygen-containing functional groups on the surface of carbon nanotubes. The presence of nitrogen can change the properties of the electron donor, thereby improving the conductivity of the carbon material; the prepared nitrogen-doped hard carbon core is light in weight, has a distinct skeleton structure, good flexibility, and can form an effective three-dimensional conductive structure; by coating the surface of the nitrogen-doped hard carbon balls with carbon nanotubes, cross-linked carbon nanotube bundles are formed on the skeleton surface, and the carbon nanotube layer has many pores, that is, a porous skeleton is formed, which is conducive to the diffusion of electrolyte, has efficient ion transmission and structural stability, can effectively promote the transport of lithium ions, and withstand Li + The high stress caused by continuous insertion / deinsertion. The mixed solution formed by the soluble copper source, the soluble cobalt source, the organic solvent and the organic ligand can form a multi-metal oxide CuCo2O4 and a porous carbon material under the second heat treatment condition, which has good conductivity and is conducive to shortening the Li + Ion transport distance, buffer volume expansion.

[0054] In some embodiments, the method for preparing a carbon nanotube dispersion comprises: mixing carbon nanotubes with a sulfuric acid solution and subjecting the mixture to condensation reflux treatment, then mixing the mixture with concentrated nitric acid, cooling the mixture and washing the mixture, collecting the solids and mixing the solids with water to obtain a carbon nanotube dispersion.

[0055] In some embodiments, in the method for preparing the carbon nanotube dispersion, the amount ratio of carbon nanotubes, sulfuric acid and concentrated nitric acid is (200-400) mg: (100-200) mL: (35-60) mL. In some embodiments, in the method for preparing the carbon nanotube dispersion, the amount ratio of carbon nanotubes, sulfuric acid and concentrated nitric acid is 200 mg: 100 mL: 35 mL, 300 mg: 150 mL: 40 mL, 350 mg: 150 mL: 50 mL or 400 mg: 200 mL: 60 mL, etc. By using carbon nanotubes, sulfuric acid and concentrated nitric acid in a suitable amount ratio, the carbon nanotubes can be fully activated.

[0056] In some embodiments, the ratio of the carbon nanotubes to the water used for washing is (200-400) mg: (800-2000) mL, including but not limited to 200 mg: 800 mL, 250 mg: 1000 mL, 300 mg: 1500 mL, 400 mg: 20000 mL, etc. Use water in an appropriate ratio to ensure the washing effect.

[0057] In some embodiments, the mixing treatment time is 12 to 48 hours, including but not limited to 12 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours, 45 hours or 48 hours, or any range between the two. In some embodiments, the temperature of the condensation reflux treatment is 60 to 100°C, including but not limited to 60°C, 70°C, 80°C, 90°C or 100°C, or any range between the two, preferably 60 to 80°C. The condensation reflux treatment time is 1 to 5 hours, including but not limited to 1 hour, 2 hours, 3 hours, 4 hours or 5 hours, or any range between the two, preferably 2 to 3 hours. The concentration of the carbon nanotube dispersion is 1 to 4 mol / L, preferably 2 to 4 mg / mL. By combining the above conditions, the treatment effect of the carbon nanotubes can be better guaranteed to obtain highly active carbon nanotubes.

[0058] In some embodiments, the mass ratio of the polyurethane foam to the carbon nanotubes is 1:(2-4), for example, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, etc.

[0059] In some embodiments, the shape of the polyurethane foam comprises a cube, and the volume of the polyurethane foam is 1 to 1.5 cm 3 including but not limited to 1cm 3 、1.1cm 3 、1.2cm 3 , 1.5cm 3 wait.

[0060] In some embodiments, the polyurethane foam is pretreated, including: washing with deionized water and anhydrous ethanol in sequence, and drying in an oven at a certain temperature for a certain time after washing, wherein the drying temperature is 60 to 80° C. and the drying time is 12 to 24 hours.

[0061] In some embodiments, the temperature of the first heat treatment is 450-550°C, including but not limited to 450°C, 480°C, 500°C, 520°C, 550°C, etc., or any range between the two. The time of the first heat treatment is 30-90 min, including but not limited to 30 min, 40 min, 50 min, 60 min, 70 min, 90 min, etc., or any range between the two. The first heat treatment is carried out under protective gas conditions, such as nitrogen, helium, argon, etc.; the heating rate of the first heat treatment is 5-10°C / min, such as 5°C / min, 6°C / min, 7°C / min, 8°C / min or 10°C / min, etc. The present invention forms a nitrogen-doped hard carbon inner core through suitable first heat treatment conditions, which has a distinct skeleton structure, good flexibility and an effective three-dimensional conductive structure; the nitrogen-containing functional groups produced by the polyurethane foam are simultaneously enriched on the oxygen-containing functional groups on the surface of the carbon nanotubes, and the presence of nitrogen can change the properties of the electron donor, thereby improving the conductivity of the carbon material; in addition, the first heat treatment causes the carbon nanotubes to form a mutually cross-linked skeleton structure with pores to facilitate the diffusion of the electrolyte, and has efficient ion transmission and structural stability.

[0062] In some embodiments, before the first heat treatment, the first drying treatment is further included; the temperature of the first drying treatment is 60-80°C, including but not limited to 60°C, 65°C, 70°C, 75°C, 80°C, etc., or any range between the two. The time of the first drying treatment is 12-24h, including but not limited to 12h, 15h, 20h or 24h, etc., or any range between the two. The first drying treatment is carried out under appropriate conditions to remove moisture.

[0063] Metal-organic frameworks (MOFs) are organic-inorganic hybrid materials that self-assemble metal ions and organic matter through coordination bonds to form intermolecular pore ligands. Generally speaking, MOFs are not suitable for direct use as electrode materials for lithium-ion batteries (LIBs) due to their poor electronic conductivity. However, due to their unique design advantages, they have been widely used as potential precursors and templates for the preparation of LIB transition metal oxides (TMOs). Transition metal oxide / carbon composites derived from MOFs usually have a carbon matrix with small particle size, good conductivity, and porous structure, which shortens the Li+ ion transmission distance and buffers volume expansion. The present invention uses heterogeneous metal MOFs as precursors, and can prepare multi-metal oxide CuCo2O4 under the conditions of the second heat treatment. Due to the synergistic effect between the metals, its electrochemical performance is better than that of single metal oxides. The present invention uses CuCo2O4 and carbon materials and composite materials as coating layers, which have good conductivity, high capacity, good capacity retention and rate capabilities, can promote the transport of lithium ions, and can withstand Li + High stress caused by continuous embedding / de-embedding.

[0064] In some embodiments, the soluble copper source includes at least one of Cu(NO3)2·3H2O and CuSO4.

[0065] In some embodiments, the soluble cobalt source includes at least one of Co(NO3)2·6H2O and CoSO4.

[0066] In some embodiments, the organic ligand comprises 2-methylimidazole.

[0067] In some embodiments, the amount ratio of the soluble copper source, the soluble cobalt source, the organic ligand and the organic solvent is (0.2-0.8) mmol: (0.5-1.6) mmol: (15-20) mmol: (25-35) mL. In some embodiments, the amount ratio of the soluble copper source, the soluble cobalt source, the organic ligand and the organic solvent includes but is not limited to 0.2 mmol: 0.5 mmol: 15 mmol: 25 mL, 0.5 mmol: 0.8 mmol: 16 mmol: 28 mL, 0.6 mmol: 01 mmol: 17 mmol: 30 mL, 0.8 mmol: 1.6 mmol: 20 mmol: 35 mL, etc., or any range value between the two.

[0068] In some embodiments, the soaking time is 10 to 15 hours, including but not limited to 10 hours, 11 hours, 12 hours, 13 hours, 15 hours, etc. The appropriate soaking time can ensure that the base material is fully soaked, so as to facilitate the coating of the mixed solution and form a high-quality coating layer.

[0069] In some embodiments, the temperature of the second heat treatment is 300-400°C, including but not limited to 300°C, 320°C, 350°C, 380°C or 400°C, or any range between the two. The time of the second heat treatment is 1-2h, such as 1h, 1.5h or 2h, or any range between the two. In some embodiments, the second heat treatment is carried out under protective gas conditions, and the heating rate of the second heat treatment is 2-10°C / min, including but not limited to 2°C / min, 5°C / min, 10°C / min, or any range between the two. The present invention forms a composite material of CuCo2O4 and carbon material on the surface of the matrix material through suitable second heat treatment conditions.

[0070] In some embodiments, before the second heat treatment, the second drying treatment is further performed; the temperature of the second drying treatment is 60 to 80°C, including but not limited to 60°C, 70°C or 80°C, or any range between the two. The time of the second drying treatment is 12 to 24 hours, including but not limited to 12 hours, 15 hours, 18 hours, 20 hours or 24 hours, or any range between the two.

[0071] In a preferred embodiment, the method for preparing the composite negative electrode comprises the following steps:

[0072] (a) 200-400 mg of carbon nanotubes are ultrasonically dispersed in 100-200 mL of sulfuric acid solution, stirred at room temperature for 12-48 h, then condensed and refluxed at a certain temperature, the temperature of the condensation reflux treatment is 60-100 ° C, the time is 1-5 h, then 35-60 mL of concentrated nitric acid is slowly added with a dropper, the temperature is maintained and refluxed for a certain time until it drops to room temperature. 800-2000 mL of deionized water is added to dilute, then filtered and washed to neutrality, and finally a carbon nanotube dispersion of a certain concentration is prepared, the concentration of the carbon nanotube dispersion is 1-4 mg / mL.

[0073] (b) The polyurethane foam is washed with deionized water and anhydrous ethanol in turn, and after washing, it is placed in an oven to dry, and then cut into blocks of a certain size; the treated polyurethane foam is fully immersed in a carbon nanotube dispersion of a certain concentration, and after the carbon nanotube dispersion is fully coated on the foam surface, it is taken out and placed in an oven for drying, the drying temperature is 60-80°C, and the drying time is 12-24h. Finally, a polyurethane foam coated with carbon nanotubes is obtained. The carbon nanotube foam is placed in a tubular furnace for the first heat treatment, and in an inert atmosphere, the temperature is raised to 450-550°C at 5-10°C / min, and heated for 30-90min. After the tubular furnace is cooled to room temperature, it is taken out to obtain a matrix material.

[0074] (c) Add 0.2-0.8 mmol of Cu(NO3)2.3H2O and 0.5-1.6 mmol of Co(NO3)2.6H2O to 25-35 mL of methanol to prepare a solution, then add 15-20 mmol of 2-methylimidazole to the prepared solution to obtain a mixed solution; soak the matrix material prepared in step (b) in the mixed solution for 10-15 hours, after soaking, take out the matrix material, wash it with methanol several times, and then place it in an oven at 60-80°C to dry for 12-24 hours to obtain the matrix material of the growth precursor. Then, the matrix material of the growth precursor is subjected to a second heat treatment in an inert atmosphere, the second heat treatment temperature is 300-400°C, the heat treatment time is 1-2 hours, and the heating rate is 2-10°C / min to obtain a composite negative electrode material.

[0075] According to another aspect of the present invention, the present invention also relates to a negative electrode sheet, comprising the composite negative electrode material, or the composite negative electrode material prepared by the preparation method of the composite negative electrode material.

[0076] The negative electrode sheet of the present invention comprises a negative electrode current collector and a negative electrode layer located on the surface of the negative electrode current collector, and the negative electrode layer contains the above-mentioned composite negative electrode material.

[0077] According to another aspect of the present invention, the present invention also relates to a battery, comprising the negative electrode sheet.

[0078] According to another aspect of the present invention, the present invention also relates to an electrical device comprising the battery.

[0079] The battery of the present invention has excellent cycle performance, rate performance and safety performance.

[0080] The following is further explained in conjunction with specific embodiments and comparative examples.

[0081] Example 1

[0082] A method for preparing a composite negative electrode material comprises the following steps:

[0083] (1) 300 mg of carbon nanotubes were ultrasonically dispersed in 130 mL of sulfuric acid solution, stirred at room temperature for 24 h, then condensed and refluxed at 80 °C, and then 40 mL of concentrated nitric acid was slowly added with a dropper, and the temperature was maintained and refluxed for 2 h, and then cooled to room temperature. 1500 mL of water was added to dilute the acid, and then the water was filtered and washed until neutral, and finally a 2 mg / mL carbon nanotube dispersion was prepared.

[0084] (2) 0.3 g of polyurethane foam was washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 60°C for 12 h. Then it was cut into 1 cm 3 The treated polyurethane foam was fully immersed in 2mg / mL of carbon nanotube dispersion. After the carbon nanotube dispersion was fully coated on the foam surface, it was taken out and placed in an oven at 60°C for 12 hours. Finally, a polyurethane foam coated with carbon nanotubes was obtained. The polyurethane foam coated with carbon nanotubes was placed in a tubular furnace, and heated to 500°C at a heating rate of 8°C / min in an argon atmosphere, and calcined for 30 minutes. When the tubular furnace was cooled to room temperature, it was taken out to obtain the matrix material (nitrogen-doped hard carbon balls interconnected by carbon nanotubes), which was marked as NHCS-CNT.

[0085] (3) 0.5 mmol of Cu(NO3)2·3H2O and 1.0 mmol of Co(NO3)2·6H2O were added to 30 mL of methanol to prepare a solution, and then 18 mmol of 2-methylimidazole was added to the prepared solution. The NHCS-CNT prepared in step (2) was placed in the mixed solution and soaked for 12 h. After the soaking was completed, the NHCS-CNT was taken out, washed with methanol for multiple times, and then placed in a 60°C oven for drying for 12 h to obtain a growth precursor NHCS-CNT. The growth precursor NHCS-CNT was then heated at 350°C in a nitrogen atmosphere at a heating rate of 5°C / min for 1.5 h to obtain a composite negative electrode material.

[0086] Example 2

[0087] A method for preparing a composite negative electrode material comprises the following steps:

[0088] (1) 300 mg of carbon nanotubes were ultrasonically dispersed in 150 mL of sulfuric acid solution, stirred at room temperature for 24 h, then condensed and refluxed at 80 °C, and then 40 mL of concentrated nitric acid was slowly added with a dropper, and the temperature was maintained and refluxed for 2 h, and then cooled to room temperature. 1500 mL of water was added to dilute the acid, and then the water was filtered and washed until neutral, and finally a 2 mg / mL carbon nanotube dispersion was prepared.

[0089] (2) 0.3 g of polyurethane foam was washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 60°C for 12 h. Then it was cut into 1 cm 3 The treated foam was fully immersed in a 2mg / mL carbon nanotube dispersion. After the carbon nanotube dispersion was fully coated on the foam surface, it was taken out and placed in an oven at 60°C for 12 hours. Finally, a polyurethane foam coated with carbon nanotubes was obtained. The carbon nanotube foam was placed in a tubular furnace, and heated to 500°C at a heating rate of 8°C / min in an argon atmosphere, and calcined for 30 minutes. When the tubular furnace was cooled to room temperature, it was taken out to obtain the matrix material (nitrogen-doped hard carbon balls interconnected by carbon nanotubes), which was marked as NHCS-CNT.

[0090] (3) First, 0.6 mmol of Cu(NO3)2·3H2O and 1.2 mmol of Co(NO3)2·6H2O were added to 30 mL of methanol to prepare a solution, and then 18 mmol of 2-methylimidazole was added to the prepared solution. The NHCS-CNT prepared in step (2) was placed in the mixed solution and soaked for 12 hours. After the soaking was completed, the NHCS-CNT was taken out, washed with methanol for multiple times, and then placed in a 60°C oven to dry for 12 hours to obtain the NHCS-CNT of the growth precursor. Then, the NHCS-CNT of the growth precursor was heated at 350°C in a nitrogen atmosphere at a heating rate of 5°C / min for 1.5 hours to obtain a composite negative electrode material.

[0091] Example 3

[0092] A method for preparing a composite negative electrode material comprises the following steps:

[0093] (1) 300 mg of carbon nanotubes were ultrasonically dispersed in 150 mL of sulfuric acid solution, stirred at room temperature for 24 h, then condensed and refluxed at 80 °C, and then 40 mL of concentrated nitric acid was slowly added with a dropper, and the temperature was maintained and refluxed for 2 h, and then cooled to room temperature. 1800 mL of water was added to dilute the acid, and then the water was filtered and washed until neutral, and finally a 2 mg / mL carbon nanotube dispersion was prepared.

[0094] (2) 0.3 g of polyurethane foam was washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 60°C for 12 h. Then it was cut into 1 cm 3 The treated foam was fully immersed in a 2mg / mL carbon nanotube dispersion. After the carbon nanotube dispersion was fully coated on the foam surface, it was taken out and placed in an oven at 60°C for 12 hours. Finally, a polyurethane foam coated with carbon nanotubes was obtained. The carbon nanotube foam was placed in a tubular furnace, and heated to 500°C at a rate of 8°C / min in an argon atmosphere, and calcined for 30 minutes. When the tubular furnace was cooled to room temperature, it was taken out to obtain the matrix material, which was marked as NHCS-CNT.

[0095] (3) 0.6 mmol of Cu(NO3)2·3H2O and 1.2 mmol of Co(NO3)2·6H2O were added to 30 mL of methanol to prepare a solution, and then 20 mmol of 2-methylimidazole was added to the prepared solution. The NHCS-CNT prepared in step (2) was placed in the mixed solution and soaked for 12 hours. After the soaking was completed, the NHCS-CNT was taken out, washed with methanol for multiple times, and then placed in a 60°C oven to dry for 12 hours to obtain the NHCS-CNT of the growth precursor. Then, the NHCS-CNT of the growth precursor was heated at 350°C in a nitrogen atmosphere at a heating rate of 5°C / min for 1.5 hours to obtain a composite negative electrode material.

[0096] Example 4

[0097] A method for preparing a composite negative electrode material comprises the following steps:

[0098] (1) 300 mg of carbon nanotubes were ultrasonically dispersed in 150 mL of sulfuric acid solution, stirred at room temperature for 24 h, then condensed and refluxed at 80 °C, and then 45 mL of concentrated nitric acid was slowly added with a dropper, and the temperature was maintained and refluxed for 2 h, and then cooled to room temperature. 2000 mL of water was added to dilute the acid, and then the water was filtered and washed until neutral, and finally a 2 mg / mL carbon nanotube dispersion was prepared.

[0099] (2) 0.3 g of polyurethane foam was washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 60°C for 12 h. Then it was cut into 1 cm 3 The treated foam was fully immersed in a 2mg / mL carbon nanotube dispersion. After the carbon nanotube dispersion was fully coated on the foam surface, it was taken out and placed in an oven at 60°C for 12 hours. Finally, a polyurethane foam coated with carbon nanotubes was obtained. The carbon nanotube foam was placed in a tubular furnace, and heated to 500°C at a heating rate of 8°C / min in an argon atmosphere, and calcined for 30 minutes. When the tubular furnace was cooled to room temperature, it was taken out to obtain the matrix material (nitrogen-doped hard carbon balls interconnected by carbon nanotubes), which was marked as NHCS-CNT.

[0100] (3) 0.8 mmol of Cu(NO3)2·3H2O and 1.6 mmol of Co(NO3)2·6H2O were added to 30 mL of methanol to prepare a solution, and then 18 mmol of 2-methylimidazole was added to the prepared solution. The NHCS-CNT prepared in step (2) was placed in the mixed solution and soaked for 12 hours. After the soaking was completed, the NHCS-CNT was taken out, washed with methanol for multiple times, and then placed in a 60°C oven to dry for 12 hours to obtain the NHCS-CNT of the growth precursor. The NHCS-CNT of the growth precursor was then heated at 350°C in a nitrogen atmosphere at a heating rate of 5°C / min for 2 hours to obtain a composite negative electrode material.

[0101] Example 5

[0102] A method for preparing a composite negative electrode material comprises the following steps:

[0103] (1) 300 mg of carbon nanotubes were ultrasonically dispersed in 150 mL of sulfuric acid solution, stirred at room temperature for 24 h, then condensed and refluxed at 80 °C, and then 40 mL of concentrated nitric acid was slowly added with a dropper, and the temperature was maintained and refluxed for 2 h, and then cooled to room temperature. 2000 mL of water was added to dilute the acid, and then the water was filtered and washed until neutral, and finally a 2 mg / mL carbon nanotube dispersion was prepared.

[0104] (2) 0.3 g of polyurethane foam was washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 60°C for 12 h. Then it was cut into 1 cm 3 The treated foam was fully immersed in a 2mg / mL carbon nanotube dispersion. After the carbon nanotube dispersion was fully coated on the foam surface, it was taken out and placed in an oven at 60°C for 12 hours. Finally, a polyurethane foam coated with carbon nanotubes was obtained. The carbon nanotube foam was placed in a tubular furnace, and heated to 550°C at a rate of 10°C / min in an argon atmosphere, and calcined for 30 minutes. When the tubular furnace was cooled to room temperature, it was taken out to obtain a composite negative electrode material (nitrogen-doped hard carbon balls interconnected by carbon nanotubes), marked as NHCS-CNT.

[0105] (3) 0.8 mmol of Cu(NO3)2·3H2O and 1.6 mmol of Co(NO3)2·6H2O were added to 30 mL of methanol to prepare a solution, and then 20 mmol of 2-methylimidazole was added to the prepared solution. The NHCS-CNT prepared in step (2) was placed in the mixed solution and soaked for 12 hours. After the soaking was completed, the foam was taken out, washed with methanol for several times, and then placed in a 60°C oven to dry for 12 hours to obtain the NHCS-CNT growth precursor. Then, the NHCS-CNT growth precursor was heated at 350°C in a nitrogen atmosphere at a heating rate of 5°C / min for 1.5 hours to obtain a composite negative electrode material.

[0106] Example 6

[0107] A method for preparing a composite negative electrode material comprises the following steps:

[0108] (1) 300 mg of carbon nanotubes were ultrasonically dispersed in 130 mL of sulfuric acid solution, stirred at room temperature for 24 h, then condensed and refluxed at 80 °C, and then 40 mL of concentrated nitric acid was slowly added with a dropper, and the temperature was maintained and refluxed for 2 h, and then cooled to room temperature. 1500 mL of water was added to dilute the acid, and then the water was filtered and washed until neutral, and finally a 2 mg / mL carbon nanotube dispersion was prepared.

[0109] (2) 0.3 g of polyurethane foam was washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 60°C for 12 h. Then it was cut into 1 cm 3The treated foam was fully immersed in a 2mg / mL carbon nanotube dispersion. After the carbon nanotube dispersion was fully coated on the foam surface, it was taken out and placed in an oven at 60°C for 12 hours. Finally, a polyurethane foam coated with carbon nanotubes was obtained. The carbon nanotube foam was placed in a tubular furnace, and heated to 550°C at a rate of 10°C / min in an argon atmosphere, and calcined for 30 minutes. When the tubular furnace was cooled to room temperature, it was taken out to obtain a matrix material (nitrogen-doped hard carbon balls interconnected by carbon nanotubes), which was marked as NHCS-CNT.

[0110] (3) 0.8 mmol of Cu(NO3)2·3H2O and 1.6 mmol of Co(NO3)2·6H2O were added to 30 mL of methanol to prepare a solution, and then 20 mmol of 2-methylimidazole was added to the prepared solution. The NHCS-CNT prepared in step (2) was placed in the mixed solution and soaked for 12 hours. After the soaking was completed, the NHCS-CNT was taken out, washed with methanol for multiple times, and then placed in a 60°C oven for 12 hours to obtain the NHCS-CNT growth precursor. The NHCS-CNT growth precursor was then heated at 400°C in a nitrogen atmosphere at a heating rate of 10°C / min for 2 hours to obtain a composite negative electrode material.

[0111] Example 7

[0112] A method for preparing a composite negative electrode material comprises the following steps:

[0113] (1) Ultrasonic dispersion of 200 mg of carbon nanotubes in 100 mL of sulfuric acid solution was performed, and the mixture was stirred at room temperature for 15 h, and then condensed and refluxed at 100 °C. Then, 35 mL of concentrated nitric acid was slowly added with a dropper, and the temperature was maintained and refluxed for 1 h, and then cooled to room temperature. 1000 mL of water was added to dilute the acid, and then the water was filtered and washed until neutral, and finally a 4 mg / mL carbon nanotube dispersion was prepared.

[0114] (2) 0.1 g of polyurethane foam was washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 80°C for 12 h. Then it was cut into 1.5 cm 3 The treated polyurethane foam is fully immersed in the above carbon nanotube dispersion. After the carbon nanotube dispersion is fully coated on the foam surface, it is taken out and placed in an oven at 80°C for 10 hours. Finally, a polyurethane foam coated with carbon nanotubes is obtained. The polyurethane foam coated with carbon nanotubes is placed in a tubular furnace, and in an argon atmosphere, the temperature is increased to 450°C at a rate of 5°C / min, and calcined for 60 minutes. When the tubular furnace is cooled to room temperature, it is taken out to obtain the matrix material (nitrogen-doped hard carbon balls interconnected by carbon nanotubes), which is marked as NHCS-CNT.

[0115] (3) 0.5 mmol of Cu(NO3)2·3H2O and 1.0 mmol of Co(NO3)2·6H2O were added to 30 mL of methanol to prepare a solution, and then 18 mmol of 2-methylimidazole was added to the prepared solution. The NHCS-CNT prepared in step (2) was placed in the mixed solution and soaked for 15 h. After the soaking was completed, the NHCS-CNT was taken out, washed with methanol for multiple times, and then placed in an oven at 80°C for 12 h to obtain a growth precursor NHCS-CNT. The growth precursor NHCS-CNT was then heated at 350°C in a nitrogen atmosphere at a heating rate of 4°C / min for 2 h to obtain a composite negative electrode material.

[0116] Example 8

[0117] A method for preparing a composite negative electrode material comprises the following steps:

[0118] (1) Ultrasonic dispersion of 400 mg of carbon nanotubes in 200 mL of sulfuric acid solution was performed, stirred at room temperature for 12 h, then condensed and refluxed at 70 °C, and then 60 mL of concentrated nitric acid was slowly added with a dropper, and the temperature was maintained and refluxed for 2.5 h, and then cooled to room temperature. 2000 mL of water was added to dilute the acid, and then the water was filtered and washed until neutral, and finally a 3 mg / mL carbon nanotube dispersion was prepared.

[0119] (2) 0.1 g of polyurethane foam was washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 60°C for 15 h. Then it was cut into 1.2 cm 3 The treated polyurethane foam is fully immersed in the above carbon nanotube dispersion. After the carbon nanotube dispersion is fully coated on the foam surface, it is taken out and placed in an oven at 60°C for 15 hours. Finally, a polyurethane foam coated with carbon nanotubes is obtained. The polyurethane foam coated with carbon nanotubes is placed in a tubular furnace, and in an argon atmosphere, the temperature is increased to 550°C at a rate of 10°C / min, and calcined for 30 minutes. When the tubular furnace is cooled to room temperature, it is taken out to obtain a matrix material (nitrogen-doped hard carbon balls interconnected by carbon nanotubes), which is marked as NHCS-CNT.

[0120] (3) 0.5 mmol of Cu(NO3)2·3H2O and 1.0 mmol of Co(NO3)2·6H2O were added to 30 mL of methanol to prepare a solution, and then 18 mmol of 2-methylimidazole was added to the prepared solution. The NHCS-CNT prepared in step (2) was placed in the mixed solution and soaked for 13 hours. After the soaking was completed, the NHCS-CNT was taken out, washed with methanol for multiple times, and then placed in a 60°C oven for drying for 13 hours to obtain a growth precursor NHCS-CNT. The growth precursor NHCS-CNT was then heated at 400°C in a nitrogen atmosphere at a heating rate of 6°C / min for 1 hour to obtain a composite negative electrode material.

[0121] Comparative Example 1

[0122] A method for preparing a composite negative electrode material comprises the following steps:

[0123] The carbon fiber cloth (CC) was washed with distilled water, ethanol and acetone in sequence, and then dried in an oven at 60°C for later use.

[0124] 0.5mmol of Cu(NO3)2·3H2O and 1.0mmol of Co(NO3)2·6H2O were added to 30mL of methanol to prepare a solution, and then 18mmol of 2-methylimidazole was added to the prepared solution. CC was placed in the mixed solution and soaked for 12 hours. After the soaking was completed, CC was taken out, washed with methanol several times, and then placed in a 60°C oven to dry for 12 hours to obtain the CC of the growth precursor. Then the CC of the growth precursor was heated at 350°C in a nitrogen atmosphere at a heating rate of 5°C / min for 1.5 hours to obtain a composite negative electrode material.

[0125] Comparative Example 2

[0126] A method for preparing a composite negative electrode material comprises the following steps:

[0127] The carbon paper (CP) was washed with distilled water, ethanol and acetone in sequence, and then dried in an oven at 60°C for later use.

[0128] 0.5mmol of Cu(NO3)2·3H2O and 1.0mmol of Co(NO3)2·6H2O were added to 30mL of methanol to prepare a solution, and then 18mmol of 2-methylimidazole was added to the prepared solution, and the CP was placed in the mixed solution and soaked for 12 hours. After the soaking was completed, the CP was taken out, washed with methanol several times, and then placed in a 60°C oven to dry for 12 hours to obtain the CP of the growth precursor. The CP of the growth precursor was then heated at 350°C in a nitrogen atmosphere at a heating rate of 5°C / min for 1.5 hours to obtain a composite negative electrode material.

[0129] Comparative Example 3

[0130] A method for preparing a composite negative electrode material comprises the following steps:

[0131] The polyurethane foam was washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 60°C for 12 hours. Then it was cut into 1 cm 3 The polyurethane foam was placed in a tube furnace and heated at 10 °C min -1 The heating rate was increased to 550°C and calcined for 60 min. After the tube furnace was cooled to room temperature, it was taken out to obtain hard carbon balls, which were marked as HCS.

[0132] 0.8mmol Cu(NO3)2·3H2O and 1.6mmol Co(NO3)2·6H2O were added to 35mL methanol to prepare a solution, and then 20mmol 2-methylimidazole was added to the prepared solution. The prepared HCS was placed in the mixed solution and soaked for 12 hours. After the soaking was completed, the HCS was taken out, washed with methanol several times, and then placed in a 60°C oven to dry for 12 hours to obtain the growth precursor HCS. Then the growth precursor HCS was heated in a nitrogen atmosphere at 400°C for 2 hours to obtain a composite negative electrode material.

[0133] Comparative Example 4

[0134] A method for preparing a composite negative electrode material comprises the following steps:

[0135] According to steps (1) to (2) of Example 1, NHCS-CNT was obtained, and a CuCo2O4 composite material (expressed as CuCo2O4@NHCS-CNT) was prepared on the surface of NHCS-CNT by solvothermal reaction. NHCS-CNT was placed in a solution containing 0.5mmol Cu(NO3)2.3H2O, 1mmol Co(NO3)2.6H2O and 30mL methanol. The solvothermal reaction temperature was 140°C and the holding time was 6h. Finally, the solvothermal reaction product was heated at 350°C in a N2 atmosphere for 2h.

[0136] Experimental example

[0137] The composite negative electrode materials of each embodiment and comparative example were used to prepare batteries. The button battery specification was CR2032 type. The batteries were assembled in a glove box. The protective gas in the glove box was argon gas. The water and oxygen partial pressures were all lower than 1ppm. The batteries were assembled using lithium iron phosphate as the positive electrode active material, the composite negative electrode material as the negative electrode, the diaphragm as the PE diaphragm, and the electrolyte selected from Farnlight 230704B1 model.

[0138] At different current densities, the discharge capacity of the full battery prepared by the composite negative electrode material of Example 1 was tested, as shown in Table 1.

[0139] Table 1 Electrochemical performance of the battery of Example 1

[0140] magnification Capacity retention rate (relative to 0.1A / g) 0.1A / g 100% 0.2A / g 97.38% 0.5A / g 87.6% 1A / g 75.9% 2A / g 65.0% 0.1A / g (after 100 cycles) 97.38%

[0141] Table 1 shows the capacity retention rate of the full battery prepared using the composite negative electrode material of Example 1 at different current densities. As the current density increases from 0.1A / g to 2A / g, the capacity retention rates are 100%, 97.38%, 87.6%, 75.9%, and 65.0%, respectively. After 100 cycles at 0.1A / g, the capacity retention rate is 97.38%. The test of the rate performance of the composite negative electrode material of Example 1 shows that the composite negative electrode material obtained by the method of the present invention has excellent rate performance.

[0142] The coulombic efficiency of the composite negative electrode materials of various embodiments and comparative examples after 100 cycles at 0.1 A / g is shown in Table 2.

[0143] Table 2 Coulombic efficiency of composite negative electrode materials after 100 cycles at 0.1 A / g

[0144]

[0145]

[0146] It can be seen from Table 2 that the coulombic efficiency of the batteries prepared from the composite negative electrode materials in each embodiment of the present invention after 100 cycles at 0.1 A / g is higher than that of the composite negative electrode materials in Comparative Examples 1 to 4, indicating that the composite negative electrode materials of the present application can effectively improve the cycle performance, and the electrochemical performance of the composite materials in each embodiment is better than that of the composite negative electrode materials in each comparative example.

[0147] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite negative electrode material, characterized in that: It comprises a base material and a composite structure located on the surface of the base material; the base material comprises a nitrogen-doped hard carbon core and carbon nanotubes covering the nitrogen-doped hard carbon core; the composite structure comprises CuCo2O4 and carbon material.

2. The composite negative electrode material according to claim 1, characterized in that: The nitrogen-doped hard carbon core includes a spherical structure.

3. The composite negative electrode material according to claim 1, characterized in that: The carbon nanotubes are in a mutually cross-linked network structure.

4. The composite negative electrode material according to any one of claims 1 to 3, characterized in that Contains at least one of the following features (1) to (2): (1) The capacity retention rate of a battery prepared from the composite negative electrode material after 100 cycles at 0.1 A / g is greater than 94%; (2) The coulombic efficiency of a battery prepared from the composite negative electrode material after 100 cycles at 0.1 A / g is greater than 90%.

5. The method for preparing a composite negative electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The polyurethane foam is immersed in a carbon nanotube dispersion to obtain a polyurethane foam loaded with carbon nanotubes, and the polyurethane foam loaded with carbon nanotubes is subjected to a first heat treatment to obtain a matrix material; the matrix material is immersed in a mixed solution formed by a soluble copper source, a soluble cobalt source, an organic solvent and an organic ligand, and a composite negative electrode material is obtained after a second heat treatment.

6. The method for preparing a composite negative electrode material according to claim 5, characterized in that: Contains at least one of the following features (1) to (6): (1) The method for preparing the carbon nanotube dispersion comprises: mixing the carbon nanotubes with a sulfuric acid solution and subjecting the mixture to condensation reflux treatment, then mixing the carbon nanotubes with concentrated nitric acid, cooling the mixture and washing the mixture, collecting the solids and mixing the solids with water to obtain the carbon nanotube dispersion; (2) In the method for preparing the carbon nanotube dispersion, the ratio of carbon nanotubes, sulfuric acid and concentrated nitric acid is (200-400) mg: (100-200) mL: (35-60) mL; (3) In the method for preparing the carbon nanotube dispersion, the mixing time is 12 to 48 hours; (4) In the method for preparing the carbon nanotube dispersion, the temperature of the condensation reflux treatment is 60 to 100° C., and the time of the condensation reflux treatment is 1 to 5 hours; (5) The concentration of the carbon nanotube dispersion is 1 to 4 mol / L; (6) The mass ratio of the polyurethane foam to the carbon nanotubes is 1:(1-4).

7. The method for preparing a composite negative electrode material according to claim 5, characterized in that: Contains at least one of the following features (1) to (4): (1) The shape of the polyurethane foam includes a cube, and the volume of the polyurethane foam is 1 to 1.5 cm 3 ; (2) The temperature of the first heat treatment is 450-550° C., and the time of the first heat treatment is 30-90 min; (3) The first heat treatment is performed under protective gas conditions, and the heating rate of the first heat treatment is 5 to 10° C. / min; (4) Before the first heat treatment, the method further includes: a first drying treatment; the temperature of the first drying treatment is 60 to 80° C., and the time of the first drying treatment is 12 to 24 hours.

8. The method for preparing a composite negative electrode material according to claim 5, characterized in that: Contains at least one of the following features (1) to (5): (1) The soluble copper source includes at least one of Cu(NO3)2·3H2O and CuSO4; (2) The soluble cobalt source includes at least one of Co(NO3)2·6H2O and CoSO4; (3) The organic ligand includes 2-methylimidazole; (4) The usage ratio of the soluble copper source, the soluble cobalt source, the organic ligand and the organic solvent is (0.2-0.8) mmol: (0.5-1.6) mmol: (15-20) mmol: (25-35) mL; (5) The soaking time is 10 to 15 hours.

9. The method for preparing a composite negative electrode material according to claim 5, characterized in that: Contains at least one of the following features (1) to (3): (1) The temperature of the second heat treatment is 300-400° C., and the time of the second heat treatment is 1-2 hours; (2) the second heat treatment is performed under protective gas conditions, and the heating rate of the second heat treatment is 2 to 10° C. / min; (3) Before the second heat treatment, the method further includes: a second drying treatment; the temperature of the second drying treatment is 60 to 80° C., and the time of the second drying treatment is 12 to 24 hours.

10. A negative electrode sheet, characterized in that: A composite negative electrode material comprising the composite negative electrode material according to any one of claims 1 to 3, or a composite negative electrode material prepared by the preparation method of the composite negative electrode material according to any one of claims 4 to 9.

11. A battery, characterized in that: The negative electrode sheet according to claim 10 is included.

12. An electrical equipment, characterized in that: Comprising the battery of claim 11.